PENGARUH PRESTASI KERJA DAN DISIPLIN KERJA KARYAWAN TERHADAP PROMOSI JABATAN PADA PERUM JASA TIRTA I MALANG - Pudji Herijanto; Nilawati Fiernaningsih; Eko Boedhi Santoso (Adbis: Jurnal Administrasi dan Bisnis, 2019)
This research was conducted to determine the effect of Work performance and Employee Work Discipline on Promotion Position in Perum Jasa Tirta I Malang. This research is an explanatory research with a quantitative approach. The data used in this study are primary data obtained by distributing questionnaires, interviews. The sampling method uses saturated sampling with a sample of 40 people. The results of this study indicate that Work performance has a significant effect on Promotion Position. Employee Work Discipline has a significant effect on Promotion Position.